Theoretical calculations of the influence of resonant Raman scattering on the quantification of XRF spectrochemical analysis - Sanchez, Hector Jorge (2011)
In this work we present theoretical calculations of the resonant Raman scattering contributions to the background of X-ray fluorescence spectra. The main goal of the paper is to obtain a simple and reliable procedure to calculate the influence of RRS in spectrochemical analysis by X-ray fluorescence including second order enhancement processes. In order to perform the calculations, the Shiraiwa and Fujino model was used to calculate the characteristic intensities of the different atomic processes involved. In the case of polychromatic excitation over a multi-element sample of proximate atomic numbers, the calculations show that the contribution of RRS is higher than Compton scattering but lower than coherent scattering, this last process being the most important source of background in the range of the fluorescent lines. The calculated effects of enhancements are rather low and have influence only on the lightest elements of the spectra. On the other hand, the resonant Raman scattering line interferes with fluorescent peaks in the case of monochromatic excitation when elements of proximate atomic numbers are analyzed (for example Al–Si). The model proposed here allows the analysis of the different sources of background, which contribute to a better understanding of the physical processes involved in the different techniques of XRF analysis. In addition, the calculations presented here can contribute significantly to a more precise quantification of traces and minor components.